LONGITUDINAL ANALYSIS OF CHANGE IN CD4+ CELL COUNTS OF HIV-1 PATIENTS ON ANTIRETROVIRAL THERAPY (ART) IN THE BUILSA DISTRICT HOSPITAL - Adams, Mustapha; Luguterah, Albert (European Scientific Journal, ESJ, 2013)
The monitoring of CD4+ cell counts are a basis for assessing the effectiveness of most HIV treatments. Understanding the way CD4+ cells change over time could provide insight into the way Patients respond to treatment and how effective treatment is with time. In this study, we obtained secondary data from the HIV/AIDS Monitoring Program at the Builsa District hospital, in which patients were enrolled and their CD4+ cell counts were regularly monitored and thus generating repeated measures of their CD4+ cell counts. The purpose of the study was to investigate some plausible determinants of change in CD4+ cell count. Mixed effects modelling approach was used for modelling the CD4+ cell counts of the patients. The results showed that, the correlation between CD4+ cell counts at different times had a first order autoregressive moving average variance-covariance structure. The Initial CD4+ cell count of a patient, the duration of treatment and the drug type used in the treatment, were the factors that significantly determined a patient’s current CD4+ cell count.